Pengaruh Formulasi Pakan Hijauan (Kaliandra, Gamal dan Rumput Gajah) Terhadap Distribusi Protein dalam Saluran Pencernaan Domba - Firdus Firdus (Jurnal Agripet, 2008)
Feed formulation influence of forage (Caliandra calothyrsus, Gliricidia sepium and Penisetum sp.) on distribution protein in sheep digestive tractABSTRACT. It was assumed that feed formulation given to animals has an effect on digested nutrient of the animals. The purpose of this experiment is to investigate nutrient contribution mainly protein in digestive tracts of sheep by forage formulation treatment (Caliandra calothyrsus, Gliricidia sepium and Penisetum sp.). Thirty (30) sheep tails with the average body weight 15,42 kg (SD 2,68) were fed forage with the following formulation: A. Fresh Penisetum sp. (FP) and fresh Caliandra calothyrsus (FC) (7 : 3 or 70 % + 30 %), B. Fresh Penisetum sp. (FP) and fresh Gliricidia sepium (FG) (7 : 3 or 70 % + 30 %), C. Fresh Penisetum sp. (FP), fresh Caliandra calothyrsus (FC) and fresh Gliricidia sepium (FG). The experiment was conducted for 90 days and water was provided ad libitum. Parameter recorded in this experiment were distribution of protein in sheep digestive tract, covers by protein rate in rumen, omasum, abomasum, small intestine, caecum, large intestine and rectal. Data recorded were processed by covariant analysis with body weight of sheep at the early experiment treatment as a covariant. Continuation test with Tukey test. The results of this research indicated that treatment had no significant effect on protein distribution of digestive tract. It was shown by protein content in digestive tract had no significantly difference among treatments ( P 0,05), except for rectum part.